The German Social Democratic Party Between Idealistic Pro-Europeanism And Domestic Ideological Priorities In The Post-Reunification Germany - Uğur Tekiner (Ankara Avrupa Çalışmaları Dergisi)
The main thrust of this article is to examine the evolution of the Social Democratic Party of Germany (Sozialdemokratische Partei Deutschlands – SPD)’s Europhile position since German reunification from a broader ideological perspective. To this end, this study rests on the field research that entails 16 semi-structured interviews with high-profile SPD political elites and archival research on key official party documents. Based on this analysis, the main argument of this study is that the SPD encountered a growing tension between idealistic and domestic views of European integration since 1990. Under the impact of the post-reunification domestic problems and Chancellor Schröder’s assertive European policy line, the German Social Democrats’ ideology-driven doubts about European integration increased at the expense of their idealistic pro-Europeanism. Over time, this tension led to the greater prominence of ideological pragmatism in the SPD’s official European Union (EU) narrative, rendering Europe a politically and ideologically salient issue for the party.